Pengaruh Fraksi Volume dan Perlakuan Awal Terhadap Kekuatan Bending Pada Material Komposit Serat TKKS - Nur Candra Dana Agusti Candra; Jefri Aldo; Ayesha Gilang Prahara; Agung Tri Noviyanto (Universitas Muhammadiyah Metro, 2026)
This study aims to evaluate the effect of fiber volume fraction and alkali surface treatment on the bending strength of composite materials reinforced with empty fruit bunch (EFB) fibers from oil palm (TKKS). The TKKS fibers were soaked in NaOH solutions with concentrations of 2%, 4%, and 6% for fiber fractions of 20%, 40%, and 60%, respectively. The composite was fabricated using the hand lay-up method with epoxy resin as the matrix and tested using the three-point bending method based on ASTM D790. The test results showed that the 20% volume fraction treated with 2% NaOH yielded the highest average bending strength of 39.59 MPa. Meanwhile, the average strength for 40% and 60% fiber fractions were 31.88 MPa and 30.07 MPa, respectively. These findings indicate that increasing fiber volume fraction does not linearly improve mechanical performance, particularly in flexural loading. It can be concluded that the combination of 20% fiber volume fraction and 2% NaOH treatment provides the best performance in terms of bending strength for TKKS-based composites.